1997
DOI: 10.1038/nsb0197-64
|View full text |Cite
|
Sign up to set email alerts
|

The structure of MCP-1 in two crystal forms provides a rare example of variable quaternary interactions

Abstract: The X-ray crystal structure of recombinant human monocyte chemoattractant protein (MCP-1) has been solved in two crystal forms. One crystal form (P), refined to 1.85 A resolution, contains a dimer in the asymmetric unit, while the other (I) contains a monomer and was refined at 2.4 A. Although both crystal forms grow together in the same droplet, the respective quaternary structures of the protein differ dramatically. In addition, both X-ray structures differ to a similar extent from the solution structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
148
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(159 citation statements)
references
References 40 publications
10
148
1
Order By: Relevance
“…The naturally cleaved forms of MCP-2 and RANTES are also devoid of bioactivity (31,34). The function of chemokines has also been further clarified from crystal structure determination and nuclear magnetic resonance data (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). In several chemokines such as IL-8, MCP-1, MCP-2, MCP-3, eotaxin, RANTES, MIP-1␣, MIP-1␤, fractalkine, and stromal cell-derived factor-1, it has been observed that the N-terminal region is essential for functional activity and that the loop immediately following the first two cysteines in the sequence, as well as the N-terminal region, plays an important role in receptor binding.…”
Section: Discussionmentioning
confidence: 99%
“…The naturally cleaved forms of MCP-2 and RANTES are also devoid of bioactivity (31,34). The function of chemokines has also been further clarified from crystal structure determination and nuclear magnetic resonance data (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). In several chemokines such as IL-8, MCP-1, MCP-2, MCP-3, eotaxin, RANTES, MIP-1␣, MIP-1␤, fractalkine, and stromal cell-derived factor-1, it has been observed that the N-terminal region is essential for functional activity and that the loop immediately following the first two cysteines in the sequence, as well as the N-terminal region, plays an important role in receptor binding.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the structure (33,34) and calculations of the difference in solvent accessibility between monomer and dimer, we identified several candidates for mutation including Tyr 13 , Thr 10 , Val 9 , and Pro 8 ( Fig. 1).…”
Section: Y13a* Affects Receptormentioning
confidence: 99%
“…Above micromolar concentrations many form homodimers, whereas at nanomolar concentrations the monomeric form predominates in solution. High resolution structures of IL-8 (31), MGSA/GRO (32), MCP-1 (33,34), RAN-TES (35,36), and MIP-1␤ (37) have also revealed a striking correlation between chemokine class and mode of dimerization (38), suggesting that dimerization may play an important role in chemokine function. A key question, however, is whether dimerization is required for receptor binding and activation or whether it plays a more subtle role in protein stability, regu-lation, surface presentation and retention, formation of the chemotactic gradient, or other processes unrelated to chemotaxis.…”
mentioning
confidence: 99%
“…As in the screen against CCR2b (6), the only other significant effect was observed for 34P35, a mutant containing a proline (49). The figure was generated by using MOLMOL (56).…”
Section: Vv-35kda Contacts Many Of the Same Residues Of Mcp-1 That Con-mentioning
confidence: 99%